Work‐related asthma: A position paper from the Thoracic Society of Australia and New Zealand and the National Asthma Council Australia. Issue 11 (5th October 2020) - Hoy, Ryan; Burdon, Jonathan; Chen, Ling; Miles, Susan; Perret, Jennifer L; Prasad, Shivonne; Radhakrishna, Naghmeh; Rimmer, Janet; Sim, Malcolm R; Yates, Deborah; Zosky, Graeme
ABSTRACT: Work‐related asthma (WRA) is one of the most common occupational respiratory conditions, and includes asthma specifically caused by occupational exposures (OA) and asthma that is worsened by conditions at work (WEA). WRA should be considered in all adults with asthma, but especially those with new‐onset or difficult to control asthma. Improvement in asthma symptoms when away from work is suggestive of WRA. Clinical history alone is insufficient to diagnose WRA; therefore, objective investigations are required to confirm the presence of asthma and the association of asthma with work activities. Management of WRA requires pharmacotherapy similar to that of non‐WRA, however, also needs to take into account control of the causative workplace exposure. Ongoing exposure will likely lead to decline in lung function and worsening asthma control. WRA is a preventable condition but this does rely on increased awareness of WRA and thorough identification and control of all potential occupational respiratory hazards.